Coyuntura Económica - Elizabeth Aponte Jaramillo; Holmes Sánchez Rengifo; Martha Vázquez Olave; Avelino Martínez Sandoval; Lilian Andrea Carrillo-Rodríguez; Leidy Ángel Giraldo (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2006)
Coyuntura económica